Assédio moral: um estudo de caso em uma organização bancária de varejo - Vieira, Judson de Carvalho (2021)
Nowadays, banking organizations are increasingly forced to adapt to changes in technological, management and behavioral fields, in order to achieve positive results and become more competitive, although such a situational context can generate tension and conflicts in the work environment. As a result, retail banking organizations have become spaces for competition, thus facilitating behaviors and attitudes that cause conflicted conducts and even workplace bullying. In that perspective, this study aims to discuss the workplace bullying in banking organizations, based on theories, which address interpersonal conflict and its evolution to workplace bullying. Based on the literature which discusses concepts of interpersonal conflicts, workplace bullying and workplace bullying at the organizational level, this research carried out the study of two real cases, which allowed us to identify the circumstances in which workplace bullying occurred and to show, through premises, the elements, that favored the occurrence of this violence and actions that could prevent new situations of workplace bullying and improve the quality of life of employees of banking organizations